Date rape - Watkins, Christine (At issue, 2009)
Date rape: an overview / University of Kentucky Police Department -- Drugs are the culprit in many date rapes / Cynthia M. Piccolo -- Alcohol contributes to most cases of date rape / Roger Dobson and Sarah Kate Templeton -- Alcohol is not the cause of date rape / Scott Hampton -- Young men must understand what constitutes rape / Mike Hardcastle -- The definition of rape has been unfairly changed / Peter Zohrab -- The definition of rape has been duly clarified / Sherry F. Colb -- Date rapists should not be severely prosecuted / Kathleen Parker -- Date rapists should be severely prosecuted / Katherine Eastvold -- Date rape drugging is widespread in the queer community / Zak Szymanski -- Campus feminists provoke false rape accusations / David R. Usher -- Campus culture allows rape to go unpunished / Jessica Bauer -- Legislation is needed to protect rape victims / Emily Charlap -- Legislation is not needed to protect rape victims / Wendy McElroy -- People who make false rape accusations should be severely punished / Jonna M. Spilbor -- Finding justice in rape cases is difficult / Dahlia Lithwick